The Effectiveness of Lumosity-Based Cognitive Empowerment on Maher Fluid Intelligence and Cognitive Functions in Elementary School Boys - Ershadi Chahardeh, Shima; Seadatee Shamir, Aboutaleb; Zabihi, Rozita (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to determine the effectiveness of Lumosity-based cognitive empowerment in enhancing fluid intelligence among first-grade elementary school boys. The focus was on assessing improvements in various cognitive functions, including perception, reasoning, attention, memory, and processing speed, through a structured cognitive training program. Methodology: The research employed a semi-experimental design with pre-test and post-test control groups. The sample comprised 40 first-grade boys from non-profit schools in District 2 of Tehran, selected through multi-stage cluster sampling and randomly assigned to experimental and control groups. The experimental group participated in ten 60-minute sessions of Lumosity-based cognitive training. Data were collected using the Maher Multidimensional Fluid Intelligence Test (MMfTI), which measures five main components of fluid intelligence. The study also included follow-up assessments to evaluate the sustainability of cognitive gains. Findings: The results indicated significant improvements in the experimental group's fluid intelligence, particularly in attention, reasoning, and processing speed, compared to the control group. These enhancements align with the theoretical foundations of cognitive training, suggesting that the structured and adaptive nature of Lumosity games effectively stimulates cognitive processes. The findings support the hypothesis that Lumosity-based cognitive training can significantly enhance core cognitive functions in young children. Conclusion: Lumosity-based cognitive empowerment proves to be an effective tool for enhancing fluid intelligence in first-grade elementary school boys. The significant improvements in key cognitive functions highlight the potential of integrating cognitive training programs into educational curricula to boost cognitive development and academic performance. However, further research with larger samples and longer follow-up periods is necessary to validate these findings and explore the long-term effects of cognitive training.